STRATEGIC PLANNING IN ACHIEVING NET ZERO EMISSIONS: CASE OF BIOMASS COFIRING TECHNOLOGY - Anissa Rizki, Ghea; Zulmasyhur (Program Studi Ilmu Pemerintahan Universitas Islam Raden Rahmat Malang, 2024)
This study emphasizes the importance of strategic planning in achieving the Net Zero Emissions(NZE) target in 2060 using Biomass Co-firing technology with a qualitative descriptive analyticalapproach. This research focuses on the cross- sectoral cooperation needed to achieve the NZE,especially in terms of social and economic aspects. This strategy aims to reduce biomass waste by1% of total waste in the environment and reduce waste generated by boilers by 10-15%. In addition,this study notes the positive social and economic impacts arising from this strategic planning, suchas increased revenue for the biomass supplier for Co-firing. Nonetheless, research also identifieschallenges in organizational management that must be overcome. Therefore, PT. PLN Energi PrimerIndonesia must be more committed to maintaining good relations with the community to support asustainable future vision and provide prosperity for all citizens. This research provides importantinsights for stakeholders committed to achieving NZE while considering critical social andeconomic aspects.